Museum collections indicate bird defaunation in a biodiversity hotspot - Vagner Cavarzere (Biota Neotropica, 2017)
Abstract: Ipanema National Forest, southeastern Brazil, once contained 340 bird species. Forest cover suffered for centuries from log exploitation and, as a result, most of the remaining forests are now an impoverished subset of the original vegetation. We show how the bird community changed over time by comparing historical and recent records. Currently, 228 species can be recorded, for a compilation of 410 species, of which 359 are documented. Some 89 forest species with historical records failed to be detected in recent surveys. Of the 72 Atlantic Forest or Cerrado endemic species, no more than 29 (40%) are still found. The bird community changed from one which used to be related to coastline rain forests to another, which relates more to drier semideciduous forests of the interior.